Effect of Different Carbon, Nitrogen Sources and Trace Elements on Mycelial Biomass Production of Colletotrichum gloeosporioides Causing Anthracnose in Citrus - Deepika Sharma; Kumud Jarial; R. S. Jarial (International Journal of Economic Plants)
The research was conducted during October, 2022 to March, 2023 at Research Laboratory, Department of Plant Pathology, College of Horticulture and Forestry, Neri, Hamirpur, Himachal Pradesh, India to study the effect of different carbon, nitrogen sources and trace elements on the growth of Colletotrichum gloeosporioides using Czapek’s Dox broth as basal medium. In all, nine carbon sources viz., arabinose, dextrose, fructose, galactose, lactose, mannitol, starch, sucrose and xylose, six nitrogen sources viz., ammonium sulphate, asparagine, aspartic acid, potassium nitrate, sodium nitrate and urea and five different trace elements viz., ammonium molybdate, cupric sulphate, ferrous sulphate, zinc sulphate, magnesium sulphate were evaluated to see their effect on mycelial biomass production of test pathogen. All the carbon, nitrogen sources and trace elements under evaluation resulted in efficient biomass production that was compared with the mycelial biomass recorded in control devoid of any carbon, nitrogen source and trace element. Among carbon sources, maximum dry mycelial weight was recorded in arabinose (871.97 mg) followed by that in starch (575.38 mg) and sucrose (529.83 mg), among nitrogen sources in aspartic acid (643.23 mg) followed by that recorded in sodium nitrate (390.87 mg) and ammonium sulphate (479.97 mg) and among trace elements in magnesium sulphate (1432.80 mg) followed by that in zinc sulphate (600.17 mg)  and ammonium molybdate (504.20 mg) each after 14 days of incubation.